TiO2-loaded epoxy resin with improved electrical characteristics as promising insulating materials. (20th April 2020) - Zhao, Honghong; Ma, Wenjie; Zhang, Leijiang; Cui, Liru; Sun, Bojing; Wu, Mingqing; Han, Xijiang; Du, Yunchen
ABSTRACT: Epoxy resin (EP)-based composites have been widely used as a new type of insulating material in ultra-high voltage direct current transmission network. In this work, we prepare a series of TiO2 -loaded EP composites and discuss the effects of TiO2 nanoparticles on mechanical properties, and electrical properties. The results indicate that TiO2 nanoparticles can improve electrical characteristics of pure EP sample significantly. TiO2 /EP-5% (5 represented the mass percentage of TiO2 in the composites) promises the superior electrical properties than its counterparts with other filler concentration. It is believed that organic-inorganic interface formed between TiO2 nanoparticles and EP matrix can effectively facilitate the generation of interconnected channels, which provide more possibility for the dissipation of accumulated charges and fast transport of charge carries, thus decreasing the surface resistivity. Meanwhile, the superior electrical breakdown strength can be also obtained in TiO2 /EP-5%. We believe that TiO2 /EP composites may be promising insulting materials in practical applications.